ISSUES OF DEVELOPING CRITICAL THINKING OF FUTURE EDUCATORS (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the issues, challenges, and strategies associated with the development of critical thinking among future educators. In the context of modern higher education, critical thinking is not merely an academic skill but an essential professional competence that determines the ability to analyze, evaluate, and make reasoned judgments in pedagogical practice. The study discusses theoretical foundations of critical thinking, its pedagogical significance, and the role of reflective and problem-based learning in fostering it.